The Effect Of Company Size, Capital Structure And Profitability On Insurance Companies Value In Indonesian Stock Exchange - Caroline, Patheresya; Susilowati, Dwi; Nurlia, Nurlia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research was conducted with the aim of determining the influence of company size, capital structure and profitability on the value of insurance companies on the Indonesian Stock Exchange in the 2019-2022 research period. The purposive sampling method was used in this research and secondary data was obtained from the Indonesia Stock Exchange (BEI) website and resulted in a sample of 17 companies. Sampling by Purposive sampling method with the prescribed criteria of researchers. Based on the results of the T test, the Company Size is positively influential and significant to the company value. Debt to Equity Ratio has a negative and insignificant impact on the company's value and Return on Asset is negative and significant to the company's value.